Social Support and Spiritual Well-Being of Patients With Esophageal Cancer Aged Over 50 Years: The Mediating Role of Rumination - Li, Jingran; Xue, Liang; Pan, Hailong (Frontiers in Psychiatry, 2022)
Background: Spiritual well-being played an important role in helping patients cope with disease. Previous studies have investigated the association between social support and spiritual well-being, while few studies explored the relationship in patients with esophageal cancer and the mechanism behind this pathway have not been thoroughly examined. Objective: This study aimed to explore the relationship between social support and spiritual well-being of Chinese patients with esophageal cancer aged over 50 yaers and to analyze whether the relationship was mediated by rumination. Methods: A cross-sectional survey was conducted with 197 esophageal cancer patients. Participants completed the general information questionnaire, the Functional Assessment of Chronic Illness Therapy-Spiritual Scale (FACIT-Sp-12), the Chinese Event Related Rumination Inventory (ERRI-C) and the Perceived Social Support Scale (PSSS). Results: Results demonstrated that social support of patients with esophageal cancer aged over 50 years was positively correlated with spiritual well-being and deliberate rumination, and negatively correlated with intrusive rumination; spiritual well-being was positively associated with deliberate rumination and negatively correlated with intrusive rumination. The effect of social support on spiritual well-being was partially mediated by deliberate rumination and intrusive rumination. Conclusions: The findings suggest that interventions directed toward enhancing social support and deliberate rumination, and reducing the level of intrusive rumination may help patients with esophageal cancer aged over 50 years improve spiritual well-being.